DNA nanotweezers for stabilizing and dynamically lighting up a lipid raft on living cell membranes and the activation of T cells. Issue 6 (7th January 2020) - Sun, Lele; Su, Yingying; Wang, Jun-Gang; Xia, Fei; Xu, Ying; Li, Di
Abstract : We report a DNA nanotweezer that recruits raft-associated lipids, proteins and possibly endogenous cholesterol on living cell membrane. The DNA nanotweezers could activate T cell proliferation in a nonspecific activation manner. Abstract : Lipid rafts are generally considered as nanodomains on cell membranes and play important roles in signaling, viral infection, and membrane trafficking. However, the raft hypothesis is still debated with many inconsistencies because the nanoscale and transient heterogeneous raft structure creates difficulties in its location and functional analysis. In the present study, we report a DNA nanotweezer composed of a cholesterol-functionalized DNA duplex that stabilizes transient lipid rafts, which facilitate the further analysis of the raft component and its functions via other spectroscopy tools. The proposed DNA nanotweezer can induce clustering of raft-associated components (saturated lipids, membrane protein and possibly endogenous cholesterol), leading to the T cell proliferation through clustering of a T-cell antigen receptor (TCR). The flexibility of random sequence noncoding DNA provides versatile possibilities of manipulating lipid rafts and activating T cells, and thus opens new ways in a future T cell therapy.